DEVELOPMENT OF INTERACTIVE MULTIMEDIA-BASED STUDENT WORKSHEETS (LKS) TO FOSTER STUDENTS' MATHEMATICAL CREATIVE THINKING SKILLS - Riwayati, Selvi; Mardiah Syofiana; Nyayu Masyita Ariani; Relawati (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to develop a valid and practical Interactive Multimedia-Based Student Worksheet (LKS) to foster students’ mathematical creative thinking skills. The research adopts a development research design using the ADDIE model, which includes the stages of Analysis (curriculum, students, and learning material), Design, Development, Implementation, and Evaluation. Instruments used in this study consist of validation sheets for learning tools and student response questionnaires for measuring practicality. The research was conducted at SMA Negeri 6 Bengkulu City with Grade X students during the 2024/2025 academic year, focusing on the topic of arithmetic sequences and series. The results demonstrate that the developed interactive multimedia-based LKS is both valid and practical. Expert validation results indicate that the material aspect achieved an average score of 3.61 and the media aspect achieved 3.67, both categorized as “highly appropriate.” In terms of practicality, analysis of student response questionnaires yielded a score of 78.3%, which also falls into the “highly practical” category. These findings suggest that the developed LKS is a feasible and effective tool for enhancing students’ mathematical creative thinking skills in secondary education settings. Keywords: Interactive Multimedia-Based Student Worksheet (LKS), CreativeThinking, ADDIE Development Model